(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
This study aims to identify the role of forensic accounting in the Iraqi environment, banking stability, and to achieve this goal, we used the field survey method, as it is the most appropriate for studying the phenomenon in question and achieving its objectives. Where we selected a sample consisting of (50) male and female employees, distributed among five private banks in Baghdad governorate, namely (Ashur International Bank, Development Investment Bank, Iraqi Middle East Investment Bank, Hammurabi Commercial Bank, Khaleej Commercial Bank), and the questionnaire tool was applied to them Designed for this purpose, which consisted of two main axes The first axis includes paragraphs of questions related to the importance of forensic accounting, while the second axis revolves around its paragraphs on banking stability. At the end of the research, we reached a set of results, the most important of which is the high rate of bad debts for many private banks in Iraq during the past years as a result of weak control and audit procedures that will be used to grant credit, which threatens the stability of these banks.